Сметководствени аспекти на современите системи за мерење на резултатите од работењето: концепти, проблеми и предизвици - Серафимовска, Марина (Економски факултет, УКИМ, Скопје, 2013)
This doctoral dissertation deals with the broader aspect of the performance measurement area. It is focused on areas that are insufficiently elaborated in the literature like assessing and reviewing performance measures as well as performance measurement systems in order to achieve their continual improvement. Also, performance measurement is related with other interrelated areas in the companies such as control systems, incentives and reporting. All of these areas use information from the performance measurement systems in order to contribute to more effective control within the companies, more realistic incentives for the employees and more comprehensive reporting to the financial statements users. Defining and selecting performance measurement system is realized with contingency theory through examining the influence of the independent variables to the performance measurement system as dependent variable. In addition, the effects of performance measurement over the overall results of the companies are examined, i.e. whether they contributed to better results. Also different advantages, disadvantages and problems with which companies are faced during the performance measurement systems implementation are examined. Performance measurement systems, thereafter, are examined as a function of control systems on a way that comparison between budgeted and actual results is enabled as well as different feed-back and feed-forward control activities are undertaken. Information from the performance measurement systems also is observed as a function of incentives, i.e. it is used as a base for employees’ compensation. Therefore, it is increasingly important the right choice of performance measures and their objective calculation that will disable presenting dressed results in order to achieve better compensation. Finally, the aim of this information related with the performance measurement systems is to be included in the integrated reporting consisting of both financial and nonfinancial information about companies’ results in order to present overall operational results of the company to the different financial statements users. In the doctoral dissertation special accents is put on developing framework for assessing and reviewing performance measures and performance measurement systems which are tested in three different organizations as a case study. Suggested frameworks for assessing ad reviewing as well as suggested phases for implementation of performance measurement systems are proved as functional and useful in selected companies.
Accounting aspects of the contemporary performance measurement systems: concepts, issues and challenges
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Блажо Недев.
Keywords: contingency theory, performance measures, performance measurement systems, control, incentives, integrated reporting